TSS (Total Suspended Soil) Analysis Using GEE (Google Earth Engine) Cloud Technology In Sibolga Waters - Mardame Pangihutan Sinaga; Jono Barita Sianipar; Ady Frenly Simanullang; Goldberd Harmuda Duva Sinaga; Mila Susanty Sianipar (Journal of Applied Geospatial Information, 2023)
The TSS research using GEE Cloud Technology in Sibolga Waters was carried out from February to April 2021, Mey to July 2021, August to October 2021, and October to December 2021. The analysis was carried out using the Sentinel-2 Satellite. TSS results showed that the highest amount was 60-120 mg/liter and the lowest was 0-60 mg/l. The content of TSS is spread evenly around the edge of the Sibolga coast to the Middle of Sibolga Waters and has passed the quality standard limit according to the Minister of Environment of the Republic of Indonesia which means the Sibolga Water area is polluted and improper for drinking water as well as for fish cultivation. The result has been seasonal influence can determine the direction of the TSS distribution pattern, both tidal factors and weather conditions such as rain and dry season. The side effect on the TSS distribution pattern in Sibolga Waters causes the TSS value at high tide to be higher than at low tide. Sentinel-2 TOA Reflectance Data imagery can be used to map the TSS distribution pattern in the Sibolga Waters area.